Optical laminate and article

By using a combined structure of transparent substrate, hard coating, adhesive layer, alternating layer and evaporated anti-fouling layer in the optical laminate, the thickness and refractive index of each layer are controlled, and the vision after the pen is sliding is solved. The problem of reduced confirmation has achieved the lack of obvious color changes before and after sliding and the improvement of abrasion resistance.

CN119137511APending Publication Date: 2024-12-13DEXERIALS CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380038265.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-12
Filing Date
2023-04-20
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the touch panel of the brushstroke mode, the sliding traces after the pen slide may lead to a decrease in visual confirmation. The existing optical stack changes significantly after sliding, affecting the visual effect.

Method used

A layered structure is adopted for transparent substrate, hard coating, adhesive layer, optical functional layer and anti-fouling layer. The optical functional layer consists of alternating high-refractive index layers and low-refractive index layers. The anti-fouling layer is an evaporated film, through The combination of the sputtering film and the vapor-deposited film controls the thickness and refractive index of each layer to ensure that the b* value change Δb* value in the L*a*b* color system before and after sliding is less than 1.9.

Benefits of technology

The color changes before and after sliding are not obvious under visual inspection, which improves visual confirmation, and enhances abrasion resistance and wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119137511A_ABST
    Figure CN119137511A_ABST
Patent Text Reader

Abstract

In this optical laminate, a transparent substrate, a hard coat layer, an adhesion layer, an optical functional layer, and an antifouling layer are laminated in this order, and the absolute value of the amount of change ([Delta] b *) in the b * value in the L * a * b * color system before and after sliding of a sliding site is 1.9 or less when a sliding test is performed for 500 reciprocals at a load of 250 g using a slider having a Shore D hardness of 40 and a diameter of 0.8 mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an optical laminate and an article. This application claims priority based on Japanese Patent Application No. 2022-078796 filed in Japan on May 12, 2022, the contents of which are incorporated herein by reference. Background Art

[0002] For example, an optical laminate for anti-reflection is sometimes provided on the surface of a flat panel display (FPD), a touch panel, a solar cell, etc. The image is visually confirmed via the optical laminate, so it is required that the optical laminate does not have an adverse effect on visual confirmation. In addition, as various operating devices are touch-paneled, the optical laminate is also required to improve scratch resistance.

[0003] For example, Patent Document 1 describes that color unevenness in a display can be reduced by setting the difference between the a* value and the b* value in the CIE-Lab colorimetric system to 2 or more.

[0004] For example, Patent Document 2 describes that the pen slip resistance can be improved by optimizing the composition of the low refractive index layer to be the outermost layer.

[0005] For example, Patent Document 3 describes an article having an antireflection coating that makes surface defects caused by scratches and fingerprints less noticeable.

[0006] For example, Patent Document 4 describes an article having an abrasion-resistant layer and having excellent durability and abrasion resistance.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2019-28364

[0010] Patent Document 2: Japanese Patent Application Publication No. 2004-86196

[0011] Patent Document 3: Japanese Patent Application Publication No. 2020-126278

[0012] Patent Document 4: Japanese Patent No. 6761348 Summary of the invention

[0013] Problems to be solved by the invention

[0014] In the case of a pen-touch touch panel, a pen slides on the surface of the optical laminate, and sliding marks left by the pen may reduce the visibility of the touch panel.

[0015] The present disclosure has been made in view of the above-mentioned problems, and an object of the present disclosure is to provide an optical layered body and an article in which the color change before and after sliding is not visually noticeable.

[0016] Solutions for solving problems

[0017] In order to solve the above technical problems, the present disclosure provides the following methods.

[0018] (1) The optical laminate of the first embodiment is laminated with a transparent substrate, a hard coating layer, a bonding layer, an optical functional layer and an antifouling layer in this order. When the optical laminate is subjected to a sliding test with a load of 250 g and 500 reciprocating strokes using a sliding piece having a Shore D hardness of 40 and a diameter of 0.8 mm, the absolute value of the change Δb* value of the b* value in the L*a*b* colorimetric system before and after sliding of the sliding portion is 1.9 or less.

[0019] (2) In the optical laminate of the above scheme, the optical functional layer may include a first high refractive index layer, a first low refractive index layer, a second high refractive index layer and a second low refractive index layer in order from the side close to the adhesion layer. The refractive index of each layer in the first high refractive index layer and the second high refractive index layer is higher than the refractive index of each layer in the first low refractive index layer and the second low refractive index layer. The physical film thickness of the first high refractive index layer is greater than 10nm and less than 20nm, the physical film thickness of the first low refractive index layer is greater than 2nm and less than 15nm, and the physical film thickness of the second low refractive index layer is greater than 70nm and less than 85nm.

[0020] (3) In the optical laminate of the above scheme, the optical functional layer may include a first high refractive index layer, a first low refractive index layer, a second high refractive index layer and a second low refractive index layer in order from the side close to the adhesion layer. The refractive index of each layer in the first high refractive index layer and the second high refractive index layer is higher than the refractive index of each layer in the first low refractive index layer and the second low refractive index layer. The optical film thickness of the first high refractive index layer is greater than 20nm and less than 48.8nm, the optical film thickness of the first low refractive index layer is greater than 2.9nm and less than 21.9nm, and the optical film thickness of the second low refractive index layer is greater than 102nm and less than 124.1nm.

[0021] (4) In the optical layered body of the above aspect, the total thickness of the physical film thickness of the optical functional layer may be 170 nm to 220 nm.

[0022] (5) In the optical layered body according to the above aspect, the total thickness of the optical film thickness of the optical functional layer may be 320 nm or more and 410 nm or less.

[0023] (6) In the optical layered body according to the above aspect, the antifouling layer may have a physical film thickness of 2 nm to 10 nm.

[0024] (7) In the optical layered body according to the above aspect, the optical functional layer may be a sputtered film.

[0025] (8) In the optical layered body according to the above aspect, the antifouling layer may be a vapor-deposited film.

[0026] (9) In the optical layered body according to the above aspect, the antifouling layer may contain a fluorine compound.

[0027] (10) An article according to a second aspect includes the optical layered body according to the above aspect.

[0028] Effects of the Invention

[0029] The color change of the optical layered body and the article before and after sliding of the above embodiment is not noticeable visually. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a cross-sectional view of an example of the optical layered body according to the first embodiment. DETAILED DESCRIPTION

[0031] Hereinafter, the present embodiment will be described in detail with reference to the accompanying drawings as appropriate. The accompanying drawings used in the following description sometimes enlarge the characteristic parts for convenience in order to facilitate understanding of the characteristics, and the dimensional ratios of the various components are sometimes different from the actual ones. The materials, dimensions, etc. shown in the following description are examples, and the present disclosure is not limited thereto, and can be implemented with appropriate changes within the scope of exerting the effect.

[0032] "Optical laminate"

[0033] For the optical layered body 10 of the present embodiment, when a sliding part with a Shore D hardness of 40 and a diameter of 0.8 mm was used and a sliding test was performed 500 times with a load of 250 g, the absolute value of the change Δb* of the b* value in the L*a*b* colorimetric system before and after sliding of the sliding part was less than 1.9.

[0034] The sliding test was carried out according to the following steps. First, the optical laminate 10 was bonded to a 1 mm thick glass using a transparent adhesive sheet (manufactured by LINTEC Co., Ltd.) in such a way that the antifouling layer 5 of the optical laminate 10 was located on the surface. Then, a sliding test was carried out linearly using a polyacetal pen (the tip shape was 0.8 mmφ, and the Shore D hardness was 40) and a sliding tester (manufactured by Imoto Seisakusho). The load was 250 gf, the number of slides was 1000 times (500 reciprocations), the reciprocating distance was 50 mm, and the reciprocating speed was 2 slides per second (1 reciprocation).

[0035] In the L*a*b* color system, L* represents brightness, and a* and b* values ​​represent chromaticity. The greater the absolute value of the a* and b* values, the greater the saturation of the color of the coordinate. That is, the greater the absolute value of the a* and b* values, the brighter the color of the coordinate, and the smaller the absolute value of the a* and b* values, the closer the color of the coordinate is to the achromatic color. The +a* coordinate is the hue in the red direction, the -a* coordinate is the hue in the green direction, the +b* coordinate is the hue in the yellow direction, and the -b* coordinate is the hue in the blue direction. Color measurement is performed using light with a wavelength of more than 380nm and less than 780nm based on the standard light source D65. The incident angle of the light in the measurement of the L* value, a* value, and b* value before and after sliding relative to the measurement surface is set to 0°.

[0036] The optical laminate 10 in which the absolute value of the change Δb* of the b* value in the L*a*b* color system before and after sliding is 1.9 or less has a sliding mark that is not easily visually confirmed after the pen sliding test. As mentioned above, the parameters representing chromaticity include a* value and b* value, but the b* value has a greater impact on the visual confirmation before and after sliding. The smaller the change range of the absolute value of the change Δb* of the b* value, the smaller the impact on the visual confirmation. The absolute value of the change Δb* of the b* value is preferably 1.7 or less, and more preferably 1.3 or less.

[0037] The absolute value of the change Δa* of the a* value in the L*a*b* color system before and after sliding is preferably 3.8 or less, more preferably 2.8 or less, and further preferably 2.4 or less. The smaller the change Δa*, the less likely it is to cause a decrease in visual confirmation accompanying sliding. It should be noted that the effect of the change Δa* of the a* value before and after sliding on visual confirmation is less than the effect of the absolute value of the change Δb* of the b* value on visual confirmation.

[0038] The color difference ΔE*ab before and after sliding of the optical laminate 10 is, for example, 3.4 or less, preferably 3.2 or less, more preferably 2.9 or less, and further preferably 2.8 or less. The color difference ΔE*ab before and after sliding is given by ΔE*ab=(ΔL* 2 +Δa* 2 +Δb* 2 ) 1 / 2 Here, ΔL* is the change in brightness ΔL* before and after sliding, Δa* is the change in a* value before and after sliding, and Δb* is the change in b* value before and after sliding.

[0039] In addition, for the optical laminate 10 of the present embodiment, it is preferred that the absolute value of the change Δb* between the b* value in the L*a*b* colorimetric system of the reflected light incident at an incident angle of 5° and the b* value in the L*a*b* colorimetric system of the reflected light incident at an incident angle of 45° is 6.0 or less. The color measurement is performed using light with a wavelength of 380 nm or more and 780 nm or less based on the standard light source D65.

[0040] As described above, the coordinate of +a* is the hue in the red direction, the coordinate of -a* is the hue in the green direction, the coordinate of +b* is the hue in the yellow direction, and the coordinate of -b* is the hue in the blue direction. On the other hand, the center of the wavelength of visible light that has a high impact on visibility is located near 565nm, and its coordinates of -a* and +b* in the L*a*b* color system are the hue of the coordinate area composed of the yellow direction and the green direction. The optical laminate of the present embodiment suppresses the hue change (producing color unevenness) that is visually confirmed due to the change in the incident angle of light to the optical laminate, and suppresses the hue change in the coordinate direction composed of the yellow direction and the green direction that is easily visually confirmed, and it is not easy to visually confirm color unevenness.

[0041] The optical layered body of the present embodiment satisfies that the absolute value of the change Δb* between the b* value in the L*a*b* colorimetric system of reflected light incident at an incident angle of 5° and the b* value in the L*a*b* colorimetric system of reflected light incident at an incident angle of 45° is 6.0 or less.

[0042] In addition, for the optical layered body of the present embodiment, the b* value in the L*a*b* colorimetric system of the reflected light when incident at an incident angle of 5° and the b* value in the L*a*b* colorimetric system of the reflected light when incident at an incident angle of 45° preferably satisfy -20≤b*≤10, and more preferably satisfy -20≤b*≤0.

[0043] Moreover, for the optical layered body of the present embodiment, the a* value in the L*a*b* colorimetric system of the reflected light when incident at an incident angle of 5° and the a* value in the L*a*b* colorimetric system of the reflected light when incident at an incident angle of 45° preferably satisfy -10≤a*≤20, and more preferably satisfy -3≤a*≤6.

[0044] In addition, the optical laminate of the present embodiment also preferably satisfies the absolute value of the change amount Δa* between the a* value in the L*a*b* colorimetric system of the reflected light when incident at an incident angle of 5° and the a* value in the L*a*b* colorimetric system of the reflected light when incident at an incident angle of 45°, which is less than 10. When this condition is met, it is more difficult to visually confirm the color unevenness caused by the change in the visual confirmation angle. In addition, at this time, it is preferred that the difference between the a* value at an incident angle of 45° and the a* value at an incident angle of 5° is positive.

[0045] The b* value has a great influence on visibility and is likely to affect the hue of an object. When the change in the b* value Δb* with different visual confirmation angles is small, the hue change caused by the change in the visual confirmation angle is less likely to be visually confirmed, and color unevenness is less likely to be visually confirmed.

[0046] When the b* value satisfies -15≤b*≤10, preferably -15≤b*≤0, the change in the a* value can be hardly visually recognized. In particular, when b≤0, the change in the a* value can be hardly visually recognized.

[0047] When the a* value satisfies -10≤a*≤20, preferably -3≤a*≤6, it is possible to avoid affecting the color in the green direction where color unevenness is more easily visually recognized.

[0048] When the amount of change Δa* of the a* value is small in addition to the amount of change Δb* of the b* value, color unevenness due to a change in the viewing angle can be further less easily visually recognized.

[0049] The color difference ΔE*ab caused by the difference in the incident angle of the incident light of the optical laminate 10 is, for example, 19.4 or less, preferably 15.2 or less, more preferably 13.6 or less, and further preferably 10 or less. The color difference ΔE*ab caused by the difference in the incident angle of the incident light is obtained from the L*a*b* value of the reflected light when incident at an incident angle of 5° and the L*a*b* value of the reflected light when incident at an incident angle of 45°, by ΔE*ab=(ΔL* 2 +Δa* 2 +Δb* 2 ) 1 / 2 Here, ΔL* is the change in brightness due to the difference in the incident angle of light, Δa* is the change in a* value due to the difference in the incident angle of light, and Δb* is the change in b* value due to the difference in the incident angle of light.

[0050] Figure 1 This is a cross-sectional view of an example of the optical layered body 10 according to the first embodiment. The optical layered body 10 includes a transparent substrate 1, a hard coat layer 2, an adhesion layer 3, an optical functional layer 4, and an antifouling layer 5 laminated in this order.

[0051] (Transparent substrate)

[0052] The transparent substrate 1 is formed of a transparent material that can transmit light in the visible light region. The transparent substrate 1 is, for example, a plastic film. The constituent materials of the plastic film are, for example, polyester resins, acetate resins, polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth) acrylic resins, polyvinyl chloride resins, polyvinylidene chloride resins, polystyrene resins, polyvinyl alcohol resins, polyarylate resins, and polyphenylene sulfide resins. The transparent substrate 1 may be an inorganic substrate or a glass film.

[0053] The transparent substrate 1 is preferably made of a polyester resin, an acetate resin, a polycarbonate resin, or a polyolefin resin. For example, the transparent substrate 1 is preferably a polyethylene terephthalate (PET) substrate or a triacetyl cellulose (TAC) substrate.

[0054] It should be noted that the "transparent material" in the present invention refers to a material having a light transmittance of 80% or more in the use wavelength region within a range that does not impair the effects of the present invention. In addition, in the present embodiment, "(meth)acrylic acid" refers to methacrylic acid and acrylic acid.

[0055] The transparent substrate 1 may contain a reinforcing material as long as the optical properties are not significantly impaired. Examples of the reinforcing material include cellulose nanofibers and nanosilica.

[0056] The transparent substrate 1 may also be a film having optical and / or physical functions. Films having optical and / or physical functions include, for example, polarizing plates, phase difference compensation films, heat ray shielding films, transparent conductive films, brightness enhancement films, barrier enhancement films, lens sheets, etc. In addition, these films may also be given an antistatic function.

[0057] The thickness of the transparent substrate 1 is not particularly limited, for example, it is 25 μm or more, preferably 40 μm or more. The thickness of the transparent substrate 1 is the physical film thickness. When the thickness of the transparent substrate 1 is 25 μm or more, the rigidity of the substrate itself can be ensured, and wrinkles are not easy to occur even if stress is applied to the optical laminate 10. In addition, when the thickness of the transparent substrate 1 is 25 μm or more, wrinkles are not easy to occur even if the hard coating layer 2 is continuously formed on the transparent substrate 1, and there are fewer concerns in manufacturing. When the thickness of the transparent substrate 1 is 25 μm or more, the optical laminate 10 is not easy to curl during manufacturing and is easy to handle.

[0058] The thickness of the transparent substrate 1 is preferably 1 mm or less, more preferably 500 μm or less, and particularly preferably 300 μm or less. When the thickness of the transparent substrate 1 is 1 mm or less, the substantial optical transparency of the transparent substrate 1 can be ensured. In addition, when the thickness of the transparent substrate 1 is 1 mm or less, a film can be formed on the transparent substrate 1 in either a single sheet method or a roll-to-roll method. In particular, when the thickness of the transparent substrate 1 is 300 μm or less, when the optical laminate 10 is manufactured by a roll-to-roll method, the length of the transparent substrate 1 that can be put into a roll at one time can be lengthened. Therefore, when the thickness of the transparent substrate 1 is 300 μm or less, when the optical laminate 10 is continuously produced by a roll-to-roll method, the productivity is excellent. In addition, when the thickness of the transparent substrate 1 is 300 μm or less, it becomes an optical laminate 10 of good quality, so it is preferred.

[0059] As for the transparent substrate 1, the surface may be subjected to etching treatment and / or primer treatment such as sputtering, corona discharge, ultraviolet irradiation, electron beam irradiation, chemical conversion, oxidation, etc. in advance. By carrying out these treatments in advance, the adhesion of the hard coating layer 2 formed on the transparent substrate 1 is improved. In addition, before forming the hard coating layer 2 on the transparent substrate 1, the surface of the transparent substrate 1 may be subjected to solvent cleaning, ultrasonic cleaning, etc. as needed, thereby removing dust and cleaning the surface of the transparent substrate 1.

[0060] (Hard Coating)

[0061] The hard coating layer 2 is not particularly limited, and a known hard coating layer can be used. The hard coating layer 2 may contain, for example, a binder resin and a filler. In addition, the hard coating layer 2 may further contain a leveling agent.

[0062] The binder resin is preferably a transparent binder resin, and examples thereof include a resin that is cured by ultraviolet rays or electron beams, that is, an ionizing radiation curing resin, a thermoplastic resin, a thermosetting resin, and the like.

[0063] An example of an ionizing radiation curable resin as a binder resin is: ethyl (meth)acrylate, ethylhexyl (meth)acrylate, styrene, methylstyrene, N-vinylpyrrolidone, etc. In addition, the ionizing radiation curable resin may also be a compound having two or more unsaturated bonds. Examples of ionizing radiation curable resins having two or more unsaturated bonds include: trimethylolpropane tri(meth)acrylate, tripropylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, di(trimethylolpropane) tetra(meth)acrylate, dipentaerythritol Penta(meth)acrylate, tripentaerythritol octa(meth)acrylate, tetrapentaerythritol deca(meth)acrylate, isocyanuric acid tri(meth)acrylate, isocyanuric acid di(meth)acrylate, polyester tri(meth)acrylate, polyester di(meth)acrylate, bisphenol di(meth)acrylate, tetra(meth)acrylate diglycerol, di(meth)acrylate adamantyl, di(meth)acrylate isobornyl, dicyclopentane di(meth)acrylate, tricyclodecane di(meth)acrylate, di(trimethylolpropane) tetra(meth)acrylate and other polyfunctional compounds. Among them, the binder resin preferably uses pentaerythritol triacrylate (PETA), dipentaerythritol hexaacrylate (DPHA) and pentaerythritol tetraacrylate (PETTA). It should be noted that "(meth)acrylate" refers to methacrylate and acrylate. The ionizing radiation curable resin may be a resin obtained by modifying the above-mentioned compound with PO (propylene oxide), EO (ethylene oxide), CL (caprolactone), etc. The ionizing radiation curable resin is preferably an acrylic ultraviolet curable resin composition.

[0064] In addition, an example of a thermoplastic resin as a binder resin is: styrene resin, (meth) acrylic resin, vinyl acetate resin, vinyl ether resin, halogen-containing resin, alicyclic olefin resin, polycarbonate resin, polyester resin, polyamide resin, cellulose derivative, silicone resin, rubber or elastomer, etc. The above-mentioned thermoplastic resin is amorphous and soluble in an organic solvent (especially a general solvent that can dissolve a variety of polymers and curable compounds). In particular, from the viewpoint of transparency and weather resistance, the binder resin is preferably styrene resin, (meth) acrylic resin, alicyclic olefin resin, polyester resin, cellulose derivative (cellulose esters, etc.), etc.

[0065] Thermosetting resins used as binder resins may be, for example, phenolic resins, urea resins, diallyl phthalate resins, melamine resins, guanamine resins, unsaturated polyester resins, polyurethane resins, epoxy resins, aminoalkyd resins, melamine-urea co-condensation resins, silicone resins, polysiloxane resins (including so-called silsesquioxanes in cage-like and ladder-like forms, etc.), etc.

[0066] The hard coat layer 2 may include an organic resin and an inorganic material, or may be an organic-inorganic hybrid material. As an example, a material formed by a sol-gel method may be cited. As an inorganic material, for example, silicon dioxide, aluminum oxide, zirconium oxide, and titanium dioxide may be cited. As an organic material, for example, an acrylic resin may be cited.

[0067] The filler may be formed of an organic substance, an inorganic substance, or both. From the perspectives of anti-glare, adhesion to the optical functional layer 4 described later, and anti-blocking, the filler contained in the hard coat layer 2 may be selected from various fillers according to the purpose of the optical laminate 10. Specifically, as the filler, for example, known fillers such as silicon dioxide (Si oxide) particles, aluminum oxide (aluminum oxide) particles, and organic microparticles may be used.

[0068] When the filler is silica particles and / or alumina particles, the average particle size of the filler is, for example, 800 nm or less, preferably 100 nm or less, more preferably 40 nm or more and 70 nm or less. When the filler is organic fine particles, the average particle size of the organic fine particles is, for example, 10 μm or less, preferably 5 μm or less, more preferably 3 μm or less.

[0069] The thickness of the hard coating layer 2 is preferably 0.5 μm or more, and more preferably 1 μm or more. The thickness of the hard coating layer 2 is preferably 100 μm or less. The thickness of the hard coating layer 2 is a physical film thickness. The hard coating layer 2 may be composed of a single layer or a plurality of layers stacked together.

[0070] (Sealing layer)

[0071] The adhesion layer 3 is located between the hard coat layer 2 and the optical function layer 4. The adhesion layer 3 improves the adhesion between the hard coat layer 2 and the optical function layer 4.

[0072] The adhesion layer 3 includes, for example, any one or more selected from the following substances: metals such as silicon, nickel, chromium, tin, gold, silver, platinum, zinc, titanium, tungsten, aluminum, zirconium, palladium, and indium; alloys of these metals; oxides, fluorides, sulfides, or nitrides of these metals.

[0073] The adhesion layer 3 may also contain an inorganic oxide with a non-stoichiometric composition. The adhesion layer 3 may be, for example, a metal oxide in an oxygen-deficient state, for example, SiOx The metal oxide having (Si oxide) as the main component. The adhesion layer 3 may be composed of Si oxide alone, and in addition to Si oxide, other elements may be contained in a range of 50% by mass or less, preferably in a range of 10% by mass or less. As other elements, Na may be contained in order to improve the durability of the adhesion layer 3, and one or more elements selected from Zr, Al, and N may be contained in order to improve the hardness of the adhesion layer 3.

[0074] The thickness of the adhesive layer 3 is preferably, for example, 1 nm or more and 10 nm or less, more preferably 1 nm or more and 5 nm or less. The thickness of the adhesive layer 3 is a physical film thickness. When the thickness of the adhesive layer 3 is within the above range, the adhesion between the optical functional layer 4 and the hard coating layer 2 is improved.

[0075] (Optical functional layer)

[0076] The optical function layer 4 is a layer that exhibits an optical function. The optical function refers to a function of controlling reflection, transmission, and refraction, which are properties of light, and examples thereof include an antireflection function, a selective reflection function, an antiglare function, and a lens function.

[0077] The optical functional layer 4 is, for example, a laminated film formed by alternately stacking a high refractive index layer and a low refractive index layer from the side of the adhesion layer 3. The refractive index of the high refractive index layer is higher than that of the low refractive index layer. The refractive index of each layer in the high refractive index layer may be the same or different. The refractive index of each layer in the low refractive index layer may be the same or different.

[0078] The total number of stacked low refractive index layers and high refractive index layers in the optical function layer 4 is not particularly limited. Figure 1 As shown, the number of layers can be 4 layers, or less than 3 layers, or more than 5 layers. The total number of layers of the low refractive index layer and the high refractive index layer in the optical functional layer 4 is preferably more than 4 layers and less than 10 layers, more preferably more than 4 layers and less than 6 layers, and most preferably 4 layers. In the case where the number of layers of the optical functional layer 4 is 4 layers, the number of layers is small and the thickness is thin, so compared with the case where the number of layers is more than 5 layers, the productivity is excellent. In addition, in the case where the number of layers of the optical functional layer 4 is 4 layers, compared with the case where the number of layers is less than 3 layers, the anti-reflection property is high, and the hue of the reflected light can be further approached to neutral (achromatic).

[0079] The optical function layer 4 exhibits an antireflection function by causing interference of reflected light reflected at each interface of a laminated body in which high refractive index layers and low refractive index layers are alternately laminated, and by diffusing light incident from the antifouling layer 5 side.

[0080] Hereinafter, the following cases are cited as examples for explanation: the optical functional layer 4 is a laminated body having four layers, namely, a first high refractive index layer 41a, a first low refractive index layer 41b, a second high refractive index layer 42a, and a second low refractive index layer 42b, stacked in sequence from the side close to the adhesion layer 3. The refractive index of each layer in the first high refractive index layer 41a and the second high refractive index layer 42a is higher than the refractive index of each layer in the first low refractive index layer 41b and the second low refractive index layer 42b.

[0081] The refractive index of the first high refractive index layer 41a and the second high refractive index layer 42a is, for example, 2.00 to 2.60, or preferably 2.10 to 2.45. The refractive indexes of the first high refractive index layer 41a and the second high refractive index layer 42a may be the same or different.

[0082] As the material of the first high refractive index layer 41a and the second high refractive index layer 42a, for example, niobium pentoxide (Nb2O5, refractive index 2.33), titanium oxide (TiO2, refractive index 2.33-2.55), tungsten oxide (WO3, refractive index 2.2), cerium oxide (CeO2, refractive index 2.2), tantalum pentoxide (Ta2O5, refractive index 2.16), zinc oxide (ZnO, refractive index 2.1), indium tin oxide (ITO, refractive index 2.06), zirconium oxide (ZrO2, refractive index 2.2), etc. can be listed. The first high refractive index layer 41a and the second high refractive index layer 42a are preferably niobium pentoxide. The materials constituting the first high refractive index layer 41a and the second high refractive index layer 42a may be the same or different.

[0083] The refractive index of the first low refractive index layer 41b and the second low refractive index layer 42b is, for example, 1.20 to 1.60, or preferably 1.30 to 1.50. The refractive indexes of the first low refractive index layer 41b and the second low refractive index layer 42b may be the same or different.

[0084] The first low refractive index layer 41b and the second low refractive index layer 42b contain, for example, oxides of Si. The first low refractive index layer 41b and the second low refractive index layer 42b are, for example, layers having SiO2 (oxides of Si) as the main component. Oxides of Si are easily available and are advantageous in terms of cost. The SiO2 monolayer film is colorless and transparent. In this embodiment, the main component refers to a component that accounts for more than 50% by mass of the components contained in the layer. The refractive indexes of the first low refractive index layer 41b and the second low refractive index layer 42b may be the same or different.

[0085] In the case where the first low refractive index layer 41b and the second low refractive index layer 42b are mainly composed of Si oxide, other elements less than 50% by mass may be included. The content of other elements other than Si oxide is preferably less than 10%. Other elements are, for example, Na, Zr, Al, and N. Na improves the durability of the first low refractive index layer 41b and the second low refractive index layer 42b. Zr, Al, and N improve the hardness of the first low refractive index layer 41b and the second low refractive index layer 42b and improve alkali resistance.

[0086] The physical film thickness of the first high refractive index layer 41a is, for example, greater than 10 nm and less than 20 nm. The physical film thickness of the first high refractive index layer 41a is preferably greater than 10 nm and less than 17 nm. The optical film thickness of the first high refractive index layer 41a is, for example, greater than 20 nm and less than 48.8 nm. The optical film thickness of the first high refractive index layer 41a is preferably greater than 23.8 nm and less than 44.3 nm. The optical film thickness is the physical film thickness multiplied by the refractive index of the layer.

[0087] The physical film thickness of the first low refractive index layer 41b is, for example, 2 nm or more and 15 nm or less. The physical film thickness of the first low refractive index layer 41b is preferably 4 nm or more and 9 nm or less, more preferably 7 nm or more and 9 nm or less. The optical film thickness of the first low refractive index layer 41b is, for example, 2.9 nm or more and 21.9 nm or less. The optical film thickness of the first low refractive index layer 41b is preferably 5.8 nm or more and 13.7 nm or less, more preferably 10.22 nm or more and 13.72 nm or less.

[0088] The physical film thickness of the second high refractive index layer 42a is, for example, 30 nm or more and 110 nm or less. The physical film thickness of the second high refractive index layer 42a is preferably 74 nm or more and 102 nm or less. The optical film thickness of the second high refractive index layer 42a is, for example, 60 nm or more and 277.2 nm or less. The optical film thickness of the second high refractive index layer 42a is preferably 172.4 nm or more and 226.8 nm or less, and more preferably 172.4 nm or more and 217.9 nm or less.

[0089] The physical film thickness of the second low refractive index layer 42b is, for example, 70 nm or more and 85 nm or less. The physical film thickness of the second low refractive index layer 42b is preferably 73 nm or more and 81 nm or less. The optical film thickness of the second low refractive index layer 42b is, for example, 102 nm or more and 124.1 nm or less. The optical film thickness of the second low refractive index layer 42b is preferably 106.6 nm or more and 118.3 nm or less.

[0090] By setting the thickness of each of the first high refractive index layer 41a, the first low refractive index layer 41b, the second high refractive index layer 42a, and the second low refractive index layer 42b to within a predetermined range, an optical laminate 10 in which the b* value in the L*a*b* colorimetric system of the reflected light from the surface is not easily changed in a sliding test can be realized. At this time, the thickness of the first low refractive index layer 41b is the thinnest among the layers of the optical functional layer 4.

[0091] The total thickness of the physical film thickness of the optical functional layer 4 is, for example, more than 170nm and less than 220nm, preferably more than 180nm and less than 210nm, more preferably more than 189nm and less than 198nm. The total thickness of the optical film thickness of the optical functional layer 4 is, for example, more than 320nm and less than 410nm, preferably more than 341.4nm and less than 399.0nm, more preferably more than 362.8nm and less than 386.8nm. By the total thickness of the optical functional layer 4 being within the prescribed range, the hue of the reflected light can be made close to neutral. In addition, by the total thickness of the optical functional layer 4 being within the prescribed range, the optical laminate 10 can be efficiently produced.

[0092] Each layer of the optical function layer 4 is, for example, a sputtered film. A sputtered film is denser than a film formed by a conventional vacuum deposition method or coating method. For example, the water vapor permeability of the optical function layer 4 of the sputtered film is 1.0 g / m 2 / day or less. The dense sputtered film has a low water vapor permeability. The sputtered film is dense and is not easy to leave sliding marks. For example, even if a part of the antifouling layer 5 is peeled off due to the sliding of the pen, the optical function layer 4 is dense, and thus it is not easy to leave the trace of the sliding of the pen.

[0093] For example, a low refractive index layer 4b is disposed on the antifouling layer 5 side of the layers forming the optical function layer 4. When the low refractive index layer 4b of the optical function layer 4 is in contact with the antifouling layer 5, the antireflection performance of the optical function layer 4 is good.

[0094] (Antifouling layer)

[0095] The antifouling layer 5 is located on the surface of the optical functional layer 4 opposite to the surface in contact with the adhesion layer 3. The antifouling layer 5 is located on the outermost surface of the optical functional layer 4. The antifouling layer 5 prevents contamination of the optical functional layer 4. In addition, the antifouling layer 5 suppresses the loss of the optical functional layer 4 due to the sliding of a pen when applied to a touch panel or the like.

[0096] The antifouling layer 5 is, for example, a vapor-deposited film on which an antifouling material is vapor-deposited. The antifouling layer 5 is formed, for example, by vacuum-depositing a fluorine compound as an antifouling material on one side of the second low refractive index layer 42b constituting the optical functional layer 4. When the antifouling layer 5 contains a fluorine compound, the sliding when inputting with a pen becomes smooth, and the pen sliding resistance of the optical laminate 10 is further improved.

[0097] The fluorine compound contained in the antifouling layer 5 is, for example, a fluorine organic compound. The fluorine organic compound is, for example, a compound containing a fluorine-modified organic group and a reactive silane group (for example, alkoxysilane). Commercially available products that can be used for the antifouling layer 5 include OPTOOL DSX (manufactured by DAIKIN Co., Ltd.) and KY-100 series (manufactured by Shin-Etsu Chemical Co., Ltd.).

[0098] When the antifouling layer 5 uses a compound containing a fluorine-modified organic group and a reactive silane group (e.g., alkoxysilane), and the second low refractive index layer 42b of the optical functional layer 4 uses SiO2, a siloxane bond is formed between the silanol group as the skeleton of the fluorine-based organic compound and SiO2. The siloxane bond improves the adhesion between the optical functional layer 4 and the antifouling layer 5.

[0099] The thickness of the antifouling layer 5 is, for example, 1 nm or more and 20 nm or less, preferably 3 nm or more and 10 nm or less. The thickness of the antifouling layer is the physical film thickness. When the thickness of the antifouling layer 5 is 1 nm or more, when the optical laminate 10 is applied to a touch panel, etc., the wear resistance can be fully ensured. In addition, when the thickness of the antifouling layer 5 is 20 nm or less, the time required for evaporation is short, and efficient manufacturing is possible.

[0100] The antifouling layer 5 may contain additives such as a light stabilizer, an ultraviolet absorber, a colorant, an antistatic agent, a lubricant, a leveling agent, a defoaming agent, an antioxidant, a flame retardant, an infrared absorber, and a surfactant as necessary.

[0101] The antifouling layer 5 formed by vapor deposition is firmly bonded to the optical functional layer 4, has few gaps and is dense. Therefore, the antifouling layer 5 formed by vapor deposition exhibits different characteristics from the antifouling layer 5 formed by other methods such as coating of an antifouling material. The antifouling layer 5 formed by vapor deposition is not easily worn.

[0102] Next, the method for producing the optical layered body according to the present embodiment will be described. First, a transparent substrate 1 is prepared. The transparent substrate can be obtained by purchasing, for example, a commercially available product.

[0103] Next, a hard coating layer 2 is formed on one side of the transparent substrate 1. A slurry containing a material to be the hard coating layer 2 is applied to the transparent substrate 1, and the material to be the hard coating layer 2 is cured by a known method, thereby obtaining the hard coating layer 2. Before forming the hard coating layer 2 on the transparent substrate 1, the surface may be cleaned as needed. As a method for cleaning the surface of the transparent substrate 1, for example, solvent cleaning, ultrasonic cleaning, etc. may be cited. In order to remove dust from the surface of the transparent substrate 1 and clean the surface, it is preferred to clean the transparent substrate 1. In addition, a commercially available transparent substrate 1 formed with a hard coating layer 2 may also be purchased.

[0104] Next, the adhesion layer 3 is formed on the hard coating layer 2. The method for producing the adhesion layer 3 is not particularly limited, and the adhesion layer 3 can be produced using a known production method. The adhesion layer 3 can be formed, for example, by a sputtering method.

[0105] Next, an optical functional layer 4 is formed on the hard coat layer 2. For example, the first high refractive index layer 41a, the first low refractive index layer 41b, the second high refractive index layer 42a, and the second low refractive index layer 42b are sequentially formed on the adhesion layer 3. The first high refractive index layer 41a, the first low refractive index layer 41b, the second high refractive index layer 42a, and the second low refractive index layer 42b are respectively made, for example, using a sputtering method. As a power supply method for the sputtering method, DC (direct current), RF (high frequency) and MF (medium frequency) can be listed. In the case where the optical functional layer is composed of an oxide film, it is impossible to sputter using DC, and poor productivity using RF. Therefore, in the case where the oxide film is sputtered, as a sputtering device, a dual magnetron sputtering device of an MF power supply is preferably used. As the frequency during sputtering, it is preferably 20KHz to 60KHz. The vacuum degree during sputtering is, for example, less than 1.0Pa. When the optical function layer 4 is formed by a roll-to-roll method, the conveying speed (line speed) is set to, for example, 0.5 m / min to 20 m / min. When the optical function layer 4 is formed under such conditions, each layer of the optical function layer 4 becomes dense.

[0106] Next, the antifouling layer 5 is formed on the second low refractive index layer 42b of the optical functional layer 4. It is preferred that the surface of the optical functional layer 4 is subjected to plasma treatment before the antifouling layer 5 is formed. When the surface of the second low refractive index layer 42 is modified by plasma treatment, the adhesion between the optical functional layer 4 and the antifouling layer 5 is improved. The cumulative output during plasma treatment is preferably 130 W·min / m 2 Above and 2000W·min / m 2 By being within this range, the sliding resistance is improved.

[0107] The antifouling layer 5 is formed, for example, by vapor deposition. The vapor deposition is performed by heating the material to be the antifouling layer 5 to a vapor pressure temperature. The vacuum degree during vapor deposition is, for example, below 1.0 Pa. When the antifouling layer 5 is formed under such conditions, the antifouling layer 5 becomes dense and is not easily worn.

[0108] The film formation of each layer of the adhesion layer 3, the optical function layer 4, and the antifouling layer 5 is preferably performed by a roll-to-roll method under a reduced pressure environment. The optical laminate 10 can be produced through the above steps.

[0109] The absolute value of the change Δb* value of the b* value in the L*a*b* colorimetric system before and after sliding of the optical laminate 10 of the first embodiment is below a predetermined value. When the change Δb* value of the b* value before and after sliding is small, although the clear reason is not known, it is difficult to visually confirm the sliding trace after the sliding test.

[0110] As mentioned above, the present invention is not limited to the above-mentioned embodiment, and various modifications and changes can be made within the scope of the gist of the present invention described in the claims.

[0111] The optical laminate 10 may also have layers other than the transparent substrate 1, the hard coating layer 2, the adhesion layer 3, the optical functional layer 4, and the antifouling layer 5. In addition, the optical laminate 10 may also have various layers as required on the surface of the transparent substrate 1 opposite to the surface on which the optical functional layer 4 is formed. For example, the optical laminate 10 may also have an adhesive layer for bonding to other components. In addition, other optical films may also be attached to the optical laminate 10 via the adhesive layer. Other optical films include, for example, polarizing films, phase difference compensation films, films that function as 1 / 2 wavelength plates, 1 / 4 wavelength plates, and the like.

[0112] In addition, a layer having functions such as anti-reflection, selective reflection, anti-glare, polarization, phase difference compensation, field angle compensation or expansion, light guiding, diffusion, brightness enhancement, hue adjustment, and electrical conductivity may be directly formed on the opposite surface of the transparent substrate 1. A moth-eye or nano-scale concave-convex structure that embodies an anti-glare function may also be formed on the surface of the optical laminate 10. Micrometer to millimeter-scale geometric shapes such as lenses and prisms may also be formed on the surface of the optical laminate 10.

[0113] In addition, the optical laminate 10 can be applied to various articles. For example, the optical laminate 10 can also be provided on the screen of an image display unit such as a liquid crystal display panel or an organic EL display panel. Thus, for example, a touch panel display unit of a smart phone or an operating device shows high scratch resistance, and an image display device suitable for actual use can be obtained.

[0114] In addition, the articles are not limited to image display devices, and the optical laminate 10 can be applied to window glass, goggles, light-receiving surfaces of solar cells, screens of smartphones, displays of personal computers, information input terminals, tablet terminals, AR (Augmented Reality) devices, VR (Virtual Reality) devices, electro-optical display panels, glass table surfaces, game consoles, operation support devices of aircraft, trains, etc., navigation systems, instrument panels, surfaces of optical sensors, etc.

[0115] Example

[0116] "Example 1"

[0117] A film made of polyethylene terephthalate (PET) with a thickness of 80 μm was prepared as a transparent substrate 1. Then, a hard coating layer 2 with a physical film thickness of 5 μm was formed on the transparent substrate 1. The hard coating layer 2 was formed by applying a coating liquid having a composition shown in Table 1 on the transparent substrate 1 using a bar coater, and irradiating it with ultraviolet rays to photopolymerize and cure it.

[0118] [Table 1]

[0119]

[0120] Next, the adhesion layer 3 and the optical function layer 4 were continuously formed on the hard coat layer 2 by reactive sputtering using a Si target and a Nb target as sputtering targets and a mixed gas of Ar gas and O 2 gas.

[0121] The physical film thickness is 3nm and the oxygen-deficient Si oxide (SiO x ) is formed as the adhesion layer 3. As for each layer of the optical functional layer 4, the first high refractive index layer 41a composed of Nb2O5, the first low refractive index layer 41b composed of SiO2, the second high refractive index layer 42a composed of Nb2O5 and the second low refractive index layer 42b composed of SiO2 are formed in sequence. The physical film thickness and optical film thickness of each layer are shown in Table 2 and Table 3. The adhesion layer 3 and the optical functional layer 4 are produced by a roll-to-roll method, and the linear speed is set to 2.0m / min. An MF dual magnetron sputtering device is used as a sputtering device, and the frequency is set to 40KHz.

[0122] Next, an antifouling layer 5 composed of the following compound, an alkoxysilane compound having a perfluoropolyether group (KY-1901, manufactured by Shin-Etsu Chemical Co., Ltd.), was formed on the optical functional layer 4 by evaporation at a pressure of 0.01 Pa or less in the evaporation chamber, a evaporation temperature of 230° C., and a line speed of 2.0 m / min. The thickness of the antifouling layer 5 was set to 5 nm. Then, the film was wound into a roll to obtain an optical laminate (antireflection film) of Example 1.

[0123] The surface roughness Ra, reflectivity, and pencil hardness of the produced optical laminate were measured. The surface roughness Ra was measured by atomic force microscopy (AFM). These results are summarized in Tables 4 and 5. The reflectivity was obtained from the reflection spectrum using a spectrophotometer (V-770 manufactured by JASCO Corporation). The pencil hardness was measured in accordance with JIS K5600-5-4.

[0124] The surface of the optical laminate is subjected to a pen sliding test. The pen sliding test is performed according to the following steps. First, the optical laminate 10 is bonded to a 1 mm thick glass using a transparent adhesive sheet (manufactured by LINTEC Co., Ltd.) in a manner such that the antifouling layer 5 is located on the surface. Then, a sliding test is performed linearly using a polyacetal pen (the tip shape is 0.8 mmφ, and the Shore D hardness is 40) using a sliding tester (manufactured by Imoto Manufacturing Co., Ltd.). The load is 250 gf, the number of slides is 1000 times (500 reciprocations), the reciprocating distance is 50 mm, and the reciprocating speed is 2 slides per second (1 reciprocation).

[0125] The chromaticity change of the reflected light before and after the sliding test was obtained as follows. A black PET film with an adhesive was attached to the back side of the glass of the pen sliding test sample, and the sample before and after sliding was measured using USPM-RU-W manufactured by Olympus Corporation. The incident light was set to be light with a wavelength of 380 nm or more and 780 nm or less based on the standard light source D65. The incident angle of the light was set to 0°. The results are shown in Tables 4 and 5.

[0126] In addition, for the obtained optical laminate, the incident angle of light relative to the surface of the optical laminate is changed to obtain the chromaticity change of the reflected light. As for the chromaticity change of the reflected light, the surface of the transparent substrate side of the optical laminate is adhered to the surface of a black acrylic panel using an acrylic transparent adhesive, and measured using a spectrophotometer (V-770 manufactured by JASCO Corporation). The incident light is set to light with a wavelength of 380nm to 780nm based on the standard light source D65. The incident angles of light are respectively 5° and 45°. The results are shown in Tables 4 and 5.

[0127] "Examples 2 to 13"

[0128] The difference between Examples 2 to 13 and Example 1 is that at least one of the material of the transparent substrate 1, the thickness of the first high refractive index layer 41a, the thickness of the first low refractive index layer 41b, the thickness of the second high refractive index layer 42a, the thickness of the second low refractive index layer 42b, the material of the first high refractive index layer 41a, the material of the second high refractive index layer 42a, and the film thickness of the antifouling layer 5 is changed. The changes different from Example 1 are summarized in Tables 2 and 3. The other conditions are the same as those of Example 1, and the same evaluation as that of Example 1 is performed. The results are summarized in Tables 4 and 5.

[0129] "Comparative Examples 1 to 4"

[0130] The difference between Comparative Examples 1 to 4 and Example 1 is that at least one of the material of the transparent substrate 1, the thickness of the first high refractive index layer 41a, the thickness of the first low refractive index layer 41b, the thickness of the second high refractive index layer 42a, and the thickness of the second low refractive index layer 42b is changed. The changes different from Example 1 are summarized in Tables 2 and 3. The other conditions are the same as those in Example 1, and the same evaluation as in Example 1 was performed. The results are summarized in Tables 4 and 5.

[0131] [Table 2]

[0132]

[0133] [Table 3]

[0134]

[0135] [Table 4]

[0136]

[0137] [Table 5]

[0138]

[0139] Regarding the visual judgment in the pen sliding test, the case where the reflected color hardly changed visually was marked as “◎”, the case where the reflected color changed slightly was marked as “○”, and the case where the reflected color changed significantly or part of the optical function layer 4 was peeled off was marked as “×”.

[0140] The determination in the angular spectrometry was performed as follows and used as a comprehensive evaluation: the case where the absolute value of the Δb* value was 6 or less was marked as "○", the case where the absolute value of the Δb* value was 6 or less and the absolute value of the Δa* value was 10 or less was marked as "◎", and the case where the |Δb*| value was 6 or more was marked as "×".

[0141] Description of Reference Numerals

[0142] 1: transparent substrate; 2: hard coating layer; 3: adhesion layer; 4: optical functional layer; 41a: first high refractive index layer; 41b: first low refractive index layer; 42a: second high refractive index layer; 42b: second low refractive index layer; 5: antifouling layer; 10: optical laminate.

Claims

1. An optical laminate, comprising a transparent substrate, a hard coating layer, an adhesion layer, an optical functional layer and an antifouling layer laminated in this order, When a sliding test was performed 500 times with a load of 250 g using a sliding part having a Shore D hardness of 40 and a diameter of 0.8 mm, the absolute value of the change in the b* value in the L*a*b* colorimetric system before and after sliding of the sliding part Δb* was less than 1.

9.

2. The optical layered body according to claim 1, wherein: The optical function layer includes, in order from the adhesion layer side, a first high refractive index layer, a first low refractive index layer, a second high refractive index layer, and a second low refractive index layer. The refractive index of each layer in the first high refractive index layer and the second high refractive index layer is higher than the refractive index of each layer in the first low refractive index layer and the second low refractive index layer. The physical film thickness of the first high refractive index layer is greater than or equal to 10 nm and less than or equal to 20 nm. The physical film thickness of the first low refractive index layer is greater than or equal to 2 nm and less than or equal to 15 nm. The physical film thickness of the second low refractive index layer is greater than or equal to 70 nm and less than or equal to 85 nm.

3. The optical layered body according to claim 1, wherein: The optical function layer includes, in order from the adhesion layer side, a first high refractive index layer, a first low refractive index layer, a second high refractive index layer, and a second low refractive index layer. The refractive index of each layer in the first high refractive index layer and the second high refractive index layer is higher than the refractive index of each layer in the first low refractive index layer and the second low refractive index layer. The optical film thickness of the first high refractive index layer is greater than or equal to 20 nm and less than or equal to 48.8 nm. The optical film thickness of the first low refractive index layer is greater than or equal to 2.9 nm and less than or equal to 21.9 nm. The optical film thickness of the second low refractive index layer is greater than or equal to 102 nm and less than or equal to 124.1 nm.

4. The optical layered body according to claim 1, wherein: The total thickness of the physical film thickness of the optical function layer is 170 nm or more and 220 nm or less.

5. The optical layered body according to claim 1, wherein: The total thickness of the optical film thickness of the optical function layer is 320 nm or more and 410 nm or less.

6. The optical layered body according to claim 1, wherein: The antifouling layer has a physical film thickness of 2 nm or more and 10 nm or less.

7. The optical layered body according to claim 1, wherein: The optical functional layer is a sputtered film.

8. The optical layered body according to claim 1, wherein: The antifouling layer is a vapor-deposited film.

9. The optical layered body according to claim 1, wherein: The antifouling layer includes a fluorine-based compound. 10 . An article comprising the optical layered body according to claim 1 .